2011
DOI: 10.1021/la203823t
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions of Proteins and Peptides at Interfaces Studied by Sum Frequency Generation Vibrational Spectroscopy

Abstract: Interfacial peptides and proteins are critical in many biological processes and thus are of interest to various research fields. To study these processes, surface sensitive techniques are required to completely describe different interfacial interactions intrinsic to many complicated processes. Sum frequency generation (SFG) spectroscopy has been developed into a powerful tool to investigate these interactions and mechanisms of a variety of interfacial peptides and proteins. It has been shown that SFG has intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 94 publications
2
69
0
1
Order By: Relevance
“…SFG can probe surfaces or interfaces which are accessible by visible and IR light in situ and in real time with sub-monolayer sensitivity. 40, 91 SFG signals characterize the molecular vibrational modes of functional groups at interfaces, which can be used to probe the interfacial presence, coverage, and orientation of various functional groups. SFG can be applied to investigate interfacial structures at a molecular level even with very low interfacial coverage.…”
Section: Introduction Of Ir + Visible Sum Frequency Generation (Sfmentioning
confidence: 99%
“…SFG can probe surfaces or interfaces which are accessible by visible and IR light in situ and in real time with sub-monolayer sensitivity. 40, 91 SFG signals characterize the molecular vibrational modes of functional groups at interfaces, which can be used to probe the interfacial presence, coverage, and orientation of various functional groups. SFG can be applied to investigate interfacial structures at a molecular level even with very low interfacial coverage.…”
Section: Introduction Of Ir + Visible Sum Frequency Generation (Sfmentioning
confidence: 99%
“…14-18 SFG is a surface sensitive second-order nonlinear optical technique and is capable of investigating interfacial structures of peptides and proteins in real time in situ . 19-25 SFG experiment only requires a very small amount of peptide and protein samples. 26-31 …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that SFG vibrational spectroscopy is capable of probing interfacial structures of a variety of polymer and biological surfaces and interfaces [53][54][55]168].…”
Section: Sfg: a Tool For The Biological Surface And Interfacementioning
confidence: 99%